“FABRICATION AND TESTING OF VARIOUS HYBRID MATERIALS KEVLAR BASALT AND CHOPPED MATE WITH HORN POWDER USING HAND LAY UP TECHNIQUE” (International Journal of Food and Nutritional Sciences, 2021)
A composite material can be defined as a combination of two or more constituent materials with different physical or chemical properties. And which remain separate and distinct on microscopic or macroscopic level within the finished structure. In other words, the constituents do not dissolve or merge into each other, although they act together to form a single material. Fiber materials have been widely used for several years and their market share is continuously growing. Composite fibers are lightweight and environmentally friendly as well as low cost compared to traditional engineering materials. The primary aim of this study was to using Basalt, chopped mate, kevlar, GOAT horn powder. By using the above mentioned three reinforcements with epoxy resin we will be provided with combinations of BASALT+10% GOAT HORN POWDER, CHOPPED MAT FIBER+10% GOAT HORN POWDER, KEVLAR FIBER+10% GOAT HORN POWDER, BASALT+ CHOPPED MAT FIBER+10% GOAT HORN POWDER, CHOPPED MAT FIBER + KEVLAR FIBER+10% GOAT HORN POWDER, KEVLAR FIBER+ BASALT FIBER+10% GOAT HORN POWDER, BASALT FIBER + CHOPPED MAT FIBER + KEVLAR FIBER + 10% GOAT HORN POWDER In all compositions commonly 10% of GOAT horn powder used. Testing such as tensile, flexural, impact, and hardness determine the properties of these composite was made the crossover material which are assessed tentatively as per ASTM norms. After which material is best consider the use real time application car bumper Create in Catia software and perform the static analysis in Ansys software finally find out the stress, strain, deformation, shear stress using best material and Gmat material.